Zinc oxide supplementation as a substitute to antibiotics in pigs (Sus scrofa domestica) - Barría, Cristian (2024)
Introduction. There is a great human concern about antibiotics resistance due to their inappropriate use as growth promoters in animal husbandry. Objective. To evaluate the effect of a high level of zinc as a substitute to antibiotics in nursery pigs. Material and methods. The study was carried out from June to August 2022 in the province of Chiriqui, Panama. The experimental period was composed of three phases with 14 days per phase. The nursery pigs (n= 54) were distributed to one of three treatments with six replicates per treatment and three pigs per replicate. The treatments were: 1) control diet, which was formulated to meet the nutritional requirements for nursery pigs; 2) similar to treatment 1, plus 200 mg of amoxicillin/kg of feed and 40 mg of florfenicol/kg of feed during phase 1 (P1) and phase 2 (P2), respectively; and 3) similar to treatment 1, plus 2000 ppm and 1600 ppm of zinc during P1 and P2, respectively. In phase 3 (P3), all pigs were fed a common diet. Results. The supplementation of zinc improved the average daily gain in all phases. Pigs fed zinc diet had better F:G ratio in P2 compared to pigs fed antibiotic diet (p < 0.05). A higher concentration of hemoglobin and percentage of monocytes was found in pigs fed with higher level of zinc than the other treatments (p < 0.05). Furthermore, Pigs fed the antibiotic, or the control diet had a lower percentage of fecal dry matter compared to those supplemented with zinc. (p < 0.05). Conclusion. The supplementation of high levels of zinc exerted improvements, in comparison to the antibiotic, in terms of hemoglobin concentration, incidence of diarrhea and weight gain in pigs during 42 days after weaning.